2006
DOI: 10.1158/0008-5472.can-06-0540
|View full text |Cite
|
Sign up to set email alerts
|

Fluorodeoxyuridine Modulates Cellular Expression of the DNA Base Excision Repair Enzyme Uracil-DNA Glycosylase

Abstract: The thymidylate synthase inhibitor 5-fluorouracil (5-FU) continues to play a pivotal role in the treatment of cancer. A downstream event of thymidylate synthase inhibition involves the induction of a self-defeating base excision repair process. With the depletion of TTP pools, there is also an increase in dUMP. Metabolism of dUMP to the triphosphate dUTP results in elevated pools of this atypical precursor for DNA synthesis. Under these conditions, there is a destructive cycle of dUMP incorporation into DNA, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 34 publications
0
32
2
Order By: Relevance
“…Note that our studies do not rule out a role for BER initiated by other DNA glycosylases such as SMUG1, TDG, and MBD4 in response to genomic 5-FU incorporation [8]. It has been reported that the nuclear isoform of UNG (UNG2) is down-regulated following FdUrd treatment in certain human cell lines, which corresponded to resistance [28]. One possible explanation of the phenotypic differences seen between cells lacking UNG2 versus hUgi-expressing cells in which UNG2 is inhibited might lie in the reported interactions between UNG2 and replication-associated proteins [5,29].…”
Section: Discussioncontrasting
confidence: 63%
“…Note that our studies do not rule out a role for BER initiated by other DNA glycosylases such as SMUG1, TDG, and MBD4 in response to genomic 5-FU incorporation [8]. It has been reported that the nuclear isoform of UNG (UNG2) is down-regulated following FdUrd treatment in certain human cell lines, which corresponded to resistance [28]. One possible explanation of the phenotypic differences seen between cells lacking UNG2 versus hUgi-expressing cells in which UNG2 is inhibited might lie in the reported interactions between UNG2 and replication-associated proteins [5,29].…”
Section: Discussioncontrasting
confidence: 63%
“…Because previous studies found widely disparate effects of modulating the functions of various UDGs in different model systems (Cortellino et al, 2003;Sansom et al, 2003;Andersen et al, 2005;Fischer et al, 2006;An et al, 2007;Kunz et al, 2009;Grogan et al, 2011;Pettersen et al, 2011;Kemmerich et al, 2012;Nagaria et al, 2012), we performed a systematic analysis in multiple human cell lines derived from tumors that are treated with and respond to 5-FU or FdUrd. In these studies, by using multiple siRNAs targeted to each UDG, we showed that UNG, and only UNG, played a role in preventing cell death after exposure to FdUrd.…”
Section: Discussionmentioning
confidence: 99%
“…Results for a representative experiment that has been performed three times are shown. Pettersen et al, 2011;Kemmerich et al, 2012;Nagaria et al, 2012) or slightly increase resistance (Fischer et al, 2006) to 5-FU or FdUrd in human, mouse, and chicken models. Similarly, studies of TDG, MBD4, and SMUG1 have also revealed discrepant results.…”
mentioning
confidence: 97%
“…The nuclear isoform of human uracil DNA glycosylase (hUNG2) was targeted for siRNA knockdown as previously described (63). The siRNA sense sequence was 5′-AUCGGCCAGAAGACGCUCUdTdT-3′ and was purchased from Dharmacon.…”
Section: Methodsmentioning
confidence: 99%